Comparative public policy - Dodds, Anneliese (New York Palgrave, 2012)
The comparative approach to public policy illuminates the policy process in both foreign and domestic contexts and also provides valuable lessons on how governments and organizations can do things differently. This new introductory text combines information about public policies in different countries with an explanation of the frameworks that have been used to analyze these policies. It compares public policies across a wide range of countries and across core policy areas, including welfare, education, healthcare and the environment. This comparison of different policy areas provides the foundation for a critical overview of the main theories and methodological issues in comparative public policy. Informed by the latest research, the text examines the key variables that lead to different policies in different countries.
Keywords: Ciencia política; Administración pública; Política comparada; Libros electrónicos